Consensus Statements on the Approach to COVID-19 Vaccine Allergy Safety in Hong Kong - Chiang, Valerie; Leung, Agnes S. Y.; Au, Elaine Y. L.; Ho, Marco H. K.; Lee, Tak Hong; Wu, Adrian Y. Y.; Wong, Gary W. K.; Li, Philip H. (Frontiers in Allergy, 2021)
Background: Mass coronavirus disease 2019 (COVID19) vaccination to achieve herd immunity is an effective means to mitigate the current COVID19 pandemic. Reports of COVID19 vaccine-associated allergic reactions and lack of clear local guidance are contributing factors leading to a low vaccine acceptance rate in our community. A Task Force of experts from the Hong Kong Institute of Allergy have been formed to address current needs. Objective: To formulate a set of consensus statements (CS) on COVID19 vaccine allergy safety (VAS) in Hong Kong. Methods: A nominated Task Force of experts managing patients with drug and vaccine allergy in Hong Kong formulated the CS by the Delphi method. Agreement was a priori defined as greater than or equal to 80% consensus. Results: A total of 11 statements met criteria for consensus with good overall agreement among Task Force members, including 7 statements on pre-vaccination recommendations and 4 statements on vaccination and post-vaccination guidance. Individuals with history of suspected allergic reaction to prior COVID19 vaccination should not receive further COVID19 vaccination, and other groups at risk of COVID19 vaccine-associated allergic reactions have been identified. Importance of pre-vaccination and post-vaccination assessment by frontline healthcare workers and evaluation by Allergists are highlighted. Conclusion: Our CS provide a pragmatic and timely guidance for local frontline healthcare providers on decisions regarding COVID19 VAS.